Exploring undergraduate experiences: A hermeneutic phenomenological study of academic internships in nursing, midwifery, and health at a northeast higher education institution in the UK (Journal of Applied Learning and Teaching, 2023)
This novel interpretative phenomenological study delves into the first-hand experiences of nursing, midwifery, and health students who undertook internship roles within a UK higher education institution during their summer break. The innovative internships in question were instrumental in facilitating the teaching of BSc (Hons) Nursing, Midwifery, and Health programmes. To our knowledge, this research marks the first exploration of such experiences among healthcare students in the UK context. As such, it contributes a new perspective to the wider body of knowledge concerning professional health education internships. With its significant and original findings, this study is poised to inform and inspire a broader discussion applicable to international settings. It can potentially influence and expand opportunities for healthcare students who aspire to work within higher education institutions, both locally and internationally.